The Influence of Transaction Costs and Opportunistic Behavior on MSME Sustainability through Operational Efficiency in Indonesia - Sri Mulyono; Junet Kaswoto; Sev Rahmiyanti; Annuridya Rosyidta Pratiwi Octasylva; Fitria Madaniah Prasetyo; Eko Sudarmanto (The Es Economics and Entrepreneurship, 2026)
This study investigates the effect of transaction costs and opportunistic behavior on the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, with operational efficiency serving as a mediating variable. A quantitative research approach was employed, involving 185 MSME respondents selected through purposive sampling. Data were collected using a structured questionnaire measured on a Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results indicate that transaction costs and opportunistic behavior have significant negative effects on both operational efficiency and MSME sustainability. Conversely, operational efficiency demonstrates a significant positive effect on sustainability and serves as a partial mediator in the relationship between transaction costs, opportunistic behavior, and MSME sustainability. These findings suggest that high transaction costs and opportunistic practices hinder business performance, while efficient operational management enhances long-term viability. The study contributes to the literature by integrating economic and behavioral perspectives within MSME sustainability research and offers practical implications for policymakers and business practitioners to improve operational performance, reduce inefficiencies, and strengthen the resilience of MSMEs in Indonesia.